When sustainable development meets international investment: Painful collision or necessary contribution? - Agata Ferreira (Economic and Environmental Studies (E&ES), 2017)
International investment has increasingly been subject to controversies and debates. Never more so then when international investment law is faced with sustainable development issues, particularly in the context of international investment arbitration. Given the characteristics of international investment law regime, and in particular the nature of its dispute resolution mechanism, types of measures challenged in the tribunals and the magnitude of monetary compensations sought by investors and frequently awarded by the tribunals, sustainable development issues become notably visible and debatable. Since sustainable development became a prominent feature of major global initiatives, political agendas and social movements, international investment disputes involving sustainable development issues gain lots of international attention. This paper aims to highlight the controversies of some of the most prominent international investment arbitration cases relating to sustainable development issues.
Keywords: K33; O44; Q56; 330; international investment law; sustainable development; international investment tribunal; investment disputes